Cartilla de orientación administrativa y contable para las peluquerías del barrio los samanes de la ciudad de Palmira (2020)
The present research work, called "Administrative and accounting guidance booklet for hairdressers in the Los Samanes neighborhood of the city of Palmira", aims to provide administrative and accounting information to the informal businesses of hairdressers, as a result of an analysis; which was carried out through a strategic diagnosis methodology through the Small Business Development Center (SBDC) -CITTGO model and criteria reference diagnoses that were identified through the DOFA Matrix.